Seismic Design Framework Based on Loss-performance Matrix. Issue 8 (11th June 2022) - Nuzzo, Iolanda; Caterino, Nicola; Pampanin, Stefano
ABSTRACT: A seismic loss-based design framework is proposed. It relies on the introduction of a multi-objective loss-performance matrix that attempts to set an innovative design approach directly associating loss measures to performance levels as a function of the design seismic intensity and the social importance of the building. This approach provides higher awareness about the economic consequences caused by structural and non-structural damage in the aftermath of an earthquake event. The design framework is applied to a case-study-reinforced concrete frame building designed as a traditional cast-in-situ moment resisting frame system, analyzing its performances within the new loss matrix.